Q: What is the factorization 4x² plus 12x plus 9?

Write your answer...

x2 + 12x + 27 = (x + 9)(x + 3)

(2x - 3)(2x - 3)

No solution. Multiply second equation by 3 and get 12x + 6y = 0 but already stated 12x + 6y = 9...

8x^3 - 12x^2 + 6x - 9 = (8x^3 - 12x^2) + (6x - 9) = 4x^2(2x - 3) + 3(2x - 3) = (4x^2 + 3)(2x - 3)

4x² - 12x + 9 = 5 → 4x² - 12x + 4 = 0 → x² - 3x + 1 = 0 → x = (-(-3) ±√((-3)² - 4×1×1))/(2×1) → x = (3 ±√5)/2 → x = (3 + √5)/2 or x = (3 - √5)/2

3x multiplied by (12x plus 9) is:3x(12x + 9)= (3x * 12x) + (3x * 9)= 36x2 + 27x

You need to rivse your question. It appears that there is not an equation here. 4*2+12x+9? You can't really solve this it is more of a statement. You can however simplify it to 12x+17- Whoever wrote this obviously can't read. It's supposed to be 4x^2+12x+9 (2x+3)(2x+3)

It is (4x-3)(4x+3) when factored

8x2 + 6x - 9 = 8x2 + 12x - 6x - 9 = 4x(2x + 3) - 3(2x + 3) = (2x + 3)(4x - 3)

If you mean: 4x squared+12x+9 then it is (2x+3)(2x+3)

12X - 7 = 4X + 9 subtract 4X from both sides 8X - 7 = 9 add 7 to both sides 8X = 16 divide both sides by 8 X = 2 check 12(2) - 7 = 4(2) + 9 24 - 7 = 8 + 9 17 = 17 checks

4x + 32x + 9 = 36x + 9

4x2 - 12x + 9 = 4x2 - 6x - 6x + 9 = 2x(2x - 3) - 3(2x - 3) = (2x - 3)(2x - 3) or (2x - 3)2

y = - 4x - 4

The value of X in the equation 3x 2-12x plus 9 is 1.25.

If you mean 12x+3y = -9 and -8x-2y = 14 then they are y = -4x-3 and y = -4x-7 respectively which means that they are parallel lines because they both have the same slope of -4 but with different y intercepts

Factor 2x plus 12x plus 28 is (x - 3)(x - 9)

The value of 64x3 + 27 depends on the value of x. If the question required factorisation, but did not ask for it, the answer is: (4x + 3)(16x2 - 12x + 9)

-5x + x + 9 = -4x + 12 -4x + 9 = -4x + 12 9 = 12 This equation has no solution.

-6 + 4x + (9-2x) = -6 + 4x + 9 - 2x = [ 3 + 2x ]

2x + 12x = 14x then include the -9 so the asnwer is 14x-9.

4x+5 = -9 4x = -9-5 4x = -14 x = -3.5

20x^2 + 27x + 9 = 0 20x^2 + 15x +12x + 9 = 0 5x(4x + 3) + 3(4x + 3) = 0 (5x + 3)(4x + 3) = 0 So either (5x + 3) = 0 which yields x = -3/5 or (4x + 3) = 0 which yields x = -3/4

write the problem: 27x4-48x2y2factor out 4x from both: 4x(27-48y)factor out the 3's: 4x * 3 (9-16y)simplify: 12x(9-16y)if you want, factor out -1 to put y in front: -12x(16y-9)both answers are correct

5x = 4x + 9 x = 9